The Coastline Change Pattern of Gresik Beach around the Madura Strait, Indonesia - Prasita, Viv Djanat; Bintoro, Rudi Siap; Permatasari, Ima Nurmalia; Widagdo, Supriyatno; Sugianto, Erik; Rosana, Nurul (Indonesian Journal of Geography, 2023)
The coastal region is characterized by dynamic changes in its coastline, which can be attributed to various factors. However, the main causes of change along the Gresik coast have yet to be thoroughly studied. Therefore, this research aims to examine the patterns of coastline change along the Gresik coast around the Madura Strait and the influence of wind-generated waves on them. Specifically, the study focuses on four coastal zones: Ujung Pangkah, Sidayu, Bungah, and Manyar districts. The research utilizes satellite imagery and geographic information systems (GIS) as well as methods for calculating ocean waves to analyze the coastline change patterns. The study also examines the impact of ocean wave energy on coastal abrasion and accretion. The findings revealed that the accretion rate in the study area was higher than the erosion rate. The accretion in the coastal area of Gresik is attributed to the flow of the Bengawan Solo River, which carries sediment from upstream. The accretion and abrasion areas for the entire period from 2002 to 2019 were 1063.16 ha and 425.23 ha, respectively. The study also found that the mangrove areas exhibit a higher rate of accretion than abrasion, indicating their potential as a reliable indicator of the effects of sea level rise resulting from global warming.This study revealed that the northern part of Ujung Pangkah District and Bungah District experienced the highest abrasion patterns, whereas no abrasion was observed in Sidayu District. Between 2002 and 2019, the abrasion areas in Ujung Pangkah and Bungah districts totaled 243.96 ha and 178.29 ha, respectively. Wind-generated waves were likely the primary cause of the abrasion in these areas, though other factors may also have contributed to coastline changes. It is essential to consider these factors for effective coastal management in the region.